2017
DOI: 10.3892/or.2017.5590
|View full text |Cite
|
Sign up to set email alerts
|

Modified Panax ginseng extract regulates autophagy by AMPK signaling in A549 human lung cancer cells

Abstract: Abstract. Panax ginseng has been used worldwide as a traditional medicine for the treatment of cancer and other diseases. The antiproliferative activity of ginseng has been increased after enzymatic processing of ginseng saponin, which may result in the accumulation of minor saponins, such as Rh2, Rg3, compound K and protopanaxatriol type (PPT) in modified regular ginseng extract (MRGX). In the present study, the anticancer activity and the associated mechanisms of MRGX were investigated using A549 human lung … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 37 publications
(34 reference statements)
0
12
0
2
Order By: Relevance
“…In contrast, plenty of studies suggested that inhibition of autophagy promoted the development of lung and liver cancers (Qu et al 2003;Yue et al 2003). Recent research found that modified regular ginseng extract (containing Rh2, Rg3, C-K and protopanaxatriol type) could induce autophagy in lung cancer cells (Yoo et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, plenty of studies suggested that inhibition of autophagy promoted the development of lung and liver cancers (Qu et al 2003;Yue et al 2003). Recent research found that modified regular ginseng extract (containing Rh2, Rg3, C-K and protopanaxatriol type) could induce autophagy in lung cancer cells (Yoo et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Chemotherapy and γ‐irradiation can inhibit cancer cell proliferation, but can also kill normal cells and cause many side effects, such as loss of immunity. Studies have shown that the five‐year survival rate in patients with lung cancer is less than 15% as a result of chemotherapy resistance; 4,5 therefore, many researchers have attempted to develop novel anticancer agents …”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the five-year survival rate in patients with lung cancer is less than 15% as a result of chemotherapy resistance; 4,5 therefore, many researchers have attempted to develop novel anticancer agents. [6][7][8] Naphthalimides are DNA intercalating agents that have shown high preclinical anticancer activity against a variety of human tumor cells. 9 Amonafide, the first naphthalimide evaluated in clinical trials as a potential anticancer agent failed to enter phase III trials because of dose-limiting bone marrow toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…This definition implies that these interventions are not fully proven to be effective or safe, nor are they based on scientific evidence. Some experimental, retrospective studies or small prospective studies have shown the potential efficacy or safety of CAM, such as oncothermia 25,26 , high-dose vitamin C 25,27 , mistletoe 11,28,29 , thymosin alpha 1 30,31 , or oriental medicine 10,12,[32][33][34] . However, some studies have shown the harmful effects of CAM, such as treatment delay, treatment refusal, and increased mortality 7,13,35 .…”
Section: Discussionmentioning
confidence: 99%